162 Doughnuts to sweet diagnosis. Issue 12 (14th November 2019) - Li, Vivien; Ingle, Gordon
Abstract : A 39-year-old professional pastry chef experienced two attacks of longitudinally extensive transverse myelitis over four years. The first presented with lower limb neuropathic pain and urinary retention. CSF was lymphocytic with raised protein and negative oligoclonal bands. MRI spine showed an inflammatory lesion from T2-8. Urinary retention improved over 2 weeks without additional therapy. Re-imaging at 12 months showed resolution of the lesion. The second episode presented with leg weakness, thoracic sensory level and urinary retention. At nadir, power was MRC grade 1–2/5 in the legs and 2–4/5 in the arms. MRI demonstrated abnormal signal and cord swelling from C3-7 and T1-4. By four weeks, power improved to 4–5/5 with IV then high dose oral corticosteroids, but genitourinary symptoms persisted. Azathioprine was later commenced with no further relapses. He is preparing to return to work, following excellent recovery of hand function. Anti-aquaporin-4 and MOG antibodies were repeatedly negative during and between attacks. However, anti-MOG antibodies were positive on re-testing a year after the second attack. While the presentation is typical, the negative result during relapses followed by a positive result while immunosuppressed and clinically stable is unusual. It highlights the value of repeated testing in leading to a defined diagnosis.